Nur Misuari an authorized biography - Stern, Tom (Anvil, 2012)
"A compelling biography of Nur Misuari. Dr. Tom Stern offers a masterful accomplishment of historical sweep, narrative and private conversations with the Moro politician and feared MNLF rebel leader, who brandished both sword and rhetoric in his more than 30 years quest for Muslim autonomy."